1990
DOI: 10.3102/00028312027004783
|View full text |Cite
|
Sign up to set email alerts
|

Costs, Effects, and Utility of Microcomputer Assisted Instruction in the Classroom

Abstract: The costs, effects, and utility of mathematics instruction assisted by microcomputer presentations were compared with those of conventional classroom approaches for grades 3 and 5. In both grades, students who received microcomputer assisted instruction scored significantly higher on a standard test of total mathematics achievement and on a test of computer literacy than did those who received conventional instruction. Students in all groups scored about the same on a survey of mathematics attitudes. In grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Testone (2005) found online homework appeared to "improve student learning and provide a better homework experience than typical textbook assignments" (p 2). The previousstudies and others (Nguyen, Hsieh,& Allen, 2006;Beal, Walles, Arroyo, & Woolf, 2007;Fletcher, Hawley,&Piele, 1990) have been conducted to examine the effects of web-based or online homework on student achievement and attitudes with a majority concluding students do derive some type of benefits from completing homework in this manner.…”
Section: Is Web-based Homework Effective?mentioning
confidence: 99%
“…Testone (2005) found online homework appeared to "improve student learning and provide a better homework experience than typical textbook assignments" (p 2). The previousstudies and others (Nguyen, Hsieh,& Allen, 2006;Beal, Walles, Arroyo, & Woolf, 2007;Fletcher, Hawley,&Piele, 1990) have been conducted to examine the effects of web-based or online homework on student achievement and attitudes with a majority concluding students do derive some type of benefits from completing homework in this manner.…”
Section: Is Web-based Homework Effective?mentioning
confidence: 99%
“…The smallest ratios provide the greatest utility for the lowest cost (Levin & McEwan, 2001). Proponents of the approach argue that when utility measures are combined with cost-effectiveness analysis, the resulting decision process more closely reflects the desires of the decision-maker than cost-effectiveness data only (Fletcher, Hawley, & Piele, 1990).…”
Section: Cost-utility Analysis In Educational Evaluationmentioning
confidence: 99%
“…Levin and McEwan (2001) found only three examples in their extensive review. Fletcher et al, (1990) conducted a cost-utility analysis that combined measurement of the outcomes of a computer assisted mathematics program; the costs of delivering the treatment and its control; and the values assigned by school board members to the gains obtained in the treatment program, relative to its increased cost. Fletcher et al concluded that the cost-utility of the computer assisted program was 55% better than the control for grade 3 and 64% better for grade 5.…”
Section: Cost-utility Analysis In Educational Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fletcher (1997) reported a limited cost-effectiveness argument for technology-based education. He presented empirical data gathered from earlier studies by Jamison et al (1976), Levin, Glass, and Meister (1987), and Fletcher, Hawley, and Piele (1990) "Intelligent tutoring systems" may be as intelligently, or unintelligently, designed as any others. They involve a capability that has been developing since the late 1960s (Carbonell, 1970) but has only recently been expanded into general use.…”
Section: G Cost Effectivenessmentioning
confidence: 99%